Characteristics and evolutionary process of low-mature paleo-subsurface rivers in carbonate sequences and controls on hydrocarbon accumulation in the northern Tarim Basin, NW China - Dong, Hongqi; Ma, Bingshan; Wan, Xiaoguo; Liang, Jiapeng; Liang, Bin; Zhang, Qingyu; Zhang, Meng; Mo, Guochen (Frontiers in Earth Science, 2025)
Paleo-subsurface rivers can serve as high-quality reservoir spaces for hydrocarbon accumulation within the carbonate sequence stratigraphy. However, the characteristics and evolutionary process of the typical low-mature paleo-subsurface rivers are rarely discussed, constraining petroleum exploration and exploitation. This study employs an integrated approach, combining seismic-geological analysis, core and thin sections, logging data, and production data within paleo-subsurface rivers to investigate the structural features and evolutionary processes of the paleo-subsurface river in the Halahatang area of the Tarim Basin, and further discuss their implications for reservoir development and hydrocarbon accumulation. The findings reveal: 1) Low-maturity paleo-subsurface rivers predominantly exhibit partially throughgoing characteristics, displaying a spatially discontinuous, downward-dipping pattern. 2) The evolutionary process of these paleo-subsurface rivers can be categorized into four distinct stages: initial isolated stage, expanded and partially through-going stage, nearly through-going stage, and condensed and partially throughgoing stage. 3) The evolution of the subsurface rivers has resulted in the segmented reservoirs, which consequently influence the compartmentalized accumulation and entrapment of hydrocarbons. The characteristics of the partially through-going subsurface rivers and their associated oil and gas reservoirs in the Halahatang area provide valuable insights for exploration and exploitation of ultra-deep carbonate reservoirs.